PEMANFAATAN TEKNOLOGI INTERNET UNTUK PEMESANAN KERIPIK SINGKONG PADA USAHA KECIL MENENGAH (UKM) DI DESA SUNGAI LANGKA - Suhada, - -; Yulmaini, - - (Jurnal Teknologi Informasi dan Bisnis Pengabdian Masyarakat Darmajaya, 2015)
Small and Medium Enterprises (SMEs) Cassava Chips Rare located in Sungai Dusun Pesawaran District 9. These SMEs engaged in culinary is processing the snacks cassava chips with the five flavors include flavor of corn roasted, cheese flavor, taste Balado, original taste and flavor barbque. Booking of cassava chips in SMEs is only done through communication of mouth to mouth, so reservations are still in a small scope. This matter is a constraint from this SMEs because only in the area around Pesawaran District alone. The method which is performed in this activity is data collection of activities using the method of observation and interviews. Web application system development method is using the System Development Life Cycle (SDLC) in the Waterfall model. The results of this activity are a Web application that can expand market reach and effectively in booking the products, so not only in the district of Pesawaran alone but can also outside the district Pesawaran.Keywords: SMEs, technology, reservations, rare river